Spend-and-tax : a panel data investigation for the EU - António Afonso; Christophe Rault (Center for Economic Studies and ifo Institute (CESifo), 2009)
Using bootstrap panel analysis, allowing for cross-country correlation, without the need of pre-testing for unit roots, we study the causality between government spending and revenue for the EU in the period 1960-2006. We find spend-and-tax causality for Italy, France, Spain, Greece, and Portugal, while tax-and-spend evidence is present for Germany, Belgium, Austria Finland and the UK, and for several EU New Member States. Moreover, in the run-up to EMU there was some shifting away from a spend-and-tax strategy, implying adjustments of fiscal behaviour.
Keywords: C23; E62; H62; 330; panel causality; fiscal policy; EU; Finanzpolitik; Steuervermeidung; Öffentliche Ausgaben; Kausalanalyse; EU-Staaten